Toxicology exposure at high altitude: is it necessary to correct toxic exposure threshold limit values? - Ramírez, Augusto V. (2011)
In occupational health to control risk magnitude we apply threshold limit values. Man at high altitude has anatomical-physiological variants in his respiratory system; most important are increases in thoracic capacity, pulmonary ventilation, alveolar/capillary diffusion, and arterial oxygen content. Physiological safe work at high altitude consists in the organism not using extra energy to compensate barometric pressure fall. In respiratory occupational toxicology we must initiate correction when ventilatory response to hypobaric hypoxia becomes unsafe and this occurs at 8 000 feet above sea level. Accordingly we should correct exposure limits value applying to work at high altitude. In order to establish safe parameters of toxicological exposition at high altitude it is necessary to investigate these aspects in high altitude workers.